The science and art of Renaissance music - Haar, James (Princeton legacy library, 1998)
As a distinguished scholar of Renaissance music, James Haar has had an abiding influence on how musicology is undertaken, owing in great measure to a substantial body of articles published over the past three decades. Collected here for the first time are representative pieces from those years, covering diverse themes of continuing interest to him and his readers: music in Renaissance culture, problems of theory as well as the Italian madrigal in the sixteenth century, the figures of Antonfrancesco Doni and Giovanthomaso Cimello, and the nineteenth century's views of early music.In this collection, the same subject is seen from several angles, and thus gives a rich context for further exploration. Haar was one of the first to recognize the value of cultural study. His work also reminds us that the close study of the music itself is equally important. The articles contained in this book show the author's conviction that a good way to address large problems is to begin by focusing on small ones.Originally published in 1998.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.